Synthesis, characterization and catalytic activity of Mn(III)- and Co(II)-salen complexes immobilized mesoporous alumina - Chaube, V. D.; Shylesh, S.; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2005)
Mn(III) and Co(II)-schiff base complexes were immobilized over mesoporous alumina through the reaction of mesoporous alumina functionalized 3-aminopropyl triethoxy silane (3-APTES) and salicylic aldehyde via schiff base condensation. The surface properties of the functionalized catalysts were analyzed by a series of characterization techniques like elemental analysis, PXRD, FTIR, N(2) adsorption-desorption, TG-DTG, DR UV-vis, XPS, etc. PXRD and adsorption-desorption analysis shows that the mesostructure of alumina remains intact after various modifications, while spectral technique show the successful anchoring of the neat complexes inside the porous alumina support. The catalytic activity of the functionalized metal-salen complexes examined in the liquid phase oxidation of styrene and cyclohexene shows that the functionalized salen complexes are more active and selective than the corresponding neat metal complexes. Further, the catalyst (Mn-S-NH(2)-MA) was recycled three times in the oxidation of styrene and no major change in the conversion and selectivity is observed, which shows that the immobilized metal-salen complexes are stable under the present reaction conditions. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Immobilization; Mesoporous alumina; Oxidation; Schiff base complexes

Sulfonic acid functionalized mesoporous silicas and organosilicas: synthesis, characterization and catalytic applications - Shylesh, S.; Samuel, Prinson P.; Srilakshmi, Ch.; Parischa, Renu; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2007)
Ethane bridged mesoporous organosilicas and MCM-41 having sulfonic acid groups in the pore channels were prepared by co-condensation method as well as grafting method, using 3-mercaptopropyltriethoxysilane (3-MPTS) as the sulfur precursor. TEM and N-2 sorption isotherm analysis revealed that the mesoporous structural ordering is retained after the functionalization and modifications of organic groups while FT-IR, Raman, XPS and solid-state C-13 CP MAS NMR shows the presence of sulfonic acid groups and the stability of the mesoporous framework. The catalytic activity of the developed materials was evaluated in the liquid phase Claisen-Schmidt condensation reaction of acetophenone with benzaldehyde, to probe the effect of mesoporous support surfaces as well as the role of preparation methods. Results showed that sulfonic acid functionalized ethane-silica samples were more active, selective and stable than the conventional sulfonic acid containing mesoporous catalysts. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: condensation; ethane-silica; heterogeneity; sulfonic acids

Synthesis of hydrothermally stable aluminium-containing ethane-silica hybrid mesoporous materials using different aluminium sources - Shylesh, S.; Samuel, Prinson P.; Singh, A. P. (Microporous and Mesoporous Materials, 2007)
Aluminium-containing ethane-silica hybrid mesoporous materials having ethane groups in the frame wall positions are synthesized using aluminium isopropoxide as well as aluminium nitrate as the aluminium sources. The materials were characterized in detail using powder XRD, N-2 adsorption-desorption, SEM, TEM, TG-DTG, TPD, Si-29, C-13 and Al-27 MAS NMR techniques. Characterization techniques revealed that aluminium isopropoxide was the appropriate source for the synthesis of organo aluminosilicas on considering the structural ordering, acidity as well as the percentage of aluminium incorporation into the ethane bridge. Al-27 MAS NMR displays aluminium as tetrahedrally coordinated in both the aluminium-containing organosilicas. Unlike the conventional EtOH-HCl template extraction process, in the present studies, we had used EtOH-NH4OH as the surfactant-extracting medium and chemical analysis results suggest that using this procedure the extent of dealumination can be greatly reduced. XRD and nitrogen physisorption studies further proved that the materials are hydrothermally stable, that the ordered pore channels retains its structure even after 150 h reflux in boiling water, while the conventional Al-MCM-41 catalyst collapsed its mesostructure after 50 h reflux in water. The improved hydrothermal stability of the hybrid materials, even in presence of sodium ions, is attributed to the thick pore walls as well as due to the presence of hydrophobic bridging ethane groups in the wall positions. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Al-HMM; Al-MCM-4l; hybrid materials; Hydrothermal stability

Synthesis and characterization of bifunctional ethenylene bridged mesoporous organoaluminosilicates - Shylesh, S.; Kapoor, Mahendra P.; Juneja, Lekh R.; Srilakshmi, Ch.; Singh, A. P. (Nanoscience and Nanotechnology Letters, 2011)
Bifunctional mesoporous organosilicas having -CH=CH- bridges and aluminium in tetrahedral coordination with tailorable pore sizes have been synthesized using a one-step templating method using cationic surfactants of different chain lengths. Unlike the conventional EtOH-HCl template extraction process, EtOH-NH(4)NO(3) was used as the surfactant-extracting medium and chemical analysis results suggest that through this procedure the mesoporous structure can be retained and dealumination can be minimized. The surfactant-extracted mesoporous solids display high surface area, pore volume and the pore size of the material varies in the range 2.6-3.6 nm, with respect to the alkyl chain length of the cationic surfactant. XRD and nitrogen physisorption studies further proved that the organosilicas are hydro thermally stable than the conventional Al-MCM-41 materials and their better stability is attributed to the thick pore walls as well as due to the presence of hydrophobic bridging ethenylene groups in the wall positions. The coupling of Al(4) with -CH=CH- bridges offer new prospects for the application of periodic mesoporous organosilicas in heterogeneous catalysis.
Keywords: Aluminium; Cationic Surfactants; Hydrothermal stability; Organosilicas